Sosialisasi Dan Pendidikan Kesehatan Program Berhenti Merokok Pada Siswa Sma Di Kota Makassar - Rosdiana, Rosdiana; Kubangun, Nur Aida; Sima, Yenny; Rahmat, Rezqiqah Aulia; Nurhedah, Nurhedah; Utami, Yuri Pratiwi; Nasution, Ahmad Faisal; Safidni, Elvira; Nurhidaya, Nurhidaya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Smoking behavior is seen from the perspective of being considered very detrimental, both for oneself and others around it. This has never subsided and seems to be a behavior that is still acceptable by society. The purpose of Community Service is to improve attitudes and knowledge of smoking cessation programs for high school students in the city of Makassar through socialization and health education. The method of implementing PkM activities used in the community service program is participatory training and role play and is carried out with a group approach, namely meetings with a group of target students. The results show that the level of knowledge increased by more than 50% after the Socialization and Health Education activities were carried out. This shows that this community service activity has succeeded in increasing students' knowledge of smoking cessation programs and prevention methods. The conclusion is that students' knowledge has increased to stop smoking based on the results of the pre-test and post-test and the PkM TEAM expects schools to provide information and socialization and health education in the form of warnings and prohibitions, especially for male students so that they are not influenced by smoking behavior from an early age, both during school hours and outside school hours.